Papa John's : use of image repair to address public relations crises - Hambrick, Marion E. (London : SAGE Publications: SAGE Business Cases Originals, 2019)
In August 2018, executives at Papa John's addressed what they hoped would be the last public relations crisis in a long list of image repair challenges dating back to November 2017. These crises included Papa John's then CEO John Schnatter publicly expressing his discontent with the National Football League and its handling of the National Anthem debate, the declining financial performance and stock price of the company, and the news of Schnatter's use of a racial slur during a company conference call. Using various image repair strategies, company leaders attempted to put the negative news behind them and focus on strategic opportunities such as improved product quality, employee training, and marketing. This case study gives readers an opportunity to evaluate Papa John's image repair process and make projections about the next moves of the company within and outside of sports.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Schnatter, John; Papa John's International, Inc; Corporate image -- Case studies; Public relations -- Case studies; Crisis management -- Case studies